Push-Out Tests on Large Diameter and High Strength Welded Stud Connectors - Fei Yang; Yuqing Liu; Yongjun Li (Advances in Civil Engineering)
In recent years, steel-concrete composite cable-pylon anchorages are increasingly employed in the construction of long-span cable-stayed bridges, especially in China. Welded stud connectors, typically 19 mm and 22 mm in diameter, are usually densely arranged at the interface between the steel anchorage box and the wall of the concrete pylon to transfer the huge cable force into the concrete pylon. However, dense welded stud arrangements at the interface have some disadvantages, such as the shear strength reduction of stud connectors and the difficulties in arranging reinforcements and pouring pylon concrete. Larger diameter and higher strength welded studs may be excellent alternatives since they both could increase the shear strength of a single stud connector and thus reduce the required number of welded studs. In this paper, push-out tests were implemented on four groups of welded stud connector specimens, including conventional 22 mm welded studs, 22 mm welded studs with much higher strength, 25 mm welded studs, and 30 mm welded studs. The shear strength, shear stiffness, and ductility of these welded stud connectors were investigated and compared with the predictions by the equations recommended in existing design codes. The results show that the shear strength of welded stud connectors could be conservatively determined by Eurocode 4, while AASHTO LRFD will produce a suitable estimation. The load-slip relationships proposed by Ollgaard and Buttry can be used to predict the load-slip curves of large diameter and high strength welded stud connectors.